2006
DOI: 10.1103/physrevd.74.055001
|View full text |Cite
|
Sign up to set email alerts
|

Top partners in little Higgs theories withTparity

Abstract: We consider a class of little Higgs theories with T -parity where all new particles responsible for canceling the standard model contributions to the one-loop quadratic divergences in the Higgs potential are odd under T -parity, including the heavy top partner which was previously taken to be T -even. The new construction significantly simplifies the spectrum in the top sector and completely changes the phenomenology of the top partner. At hadron colliders the signals of this class of T -invariant models appea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
118
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 112 publications
(120 citation statements)
references
References 47 publications
2
118
0
Order By: Relevance
“…There have been a few studies in the literature to discuss how to detect this channel at the LHC [6,21], though more detailed Monte Carlo analysis is needed to confirm how well this channel can be detected. It was also pointed out that it could be very challenging to distinguish this production channel with the top-squark (stop) pair productions predicted by the Minimal Supersymmetric Standard Model (MSSM) with the subsequent decay of stop into top quark and the lightest supersymmetric particle (neutralino) [21].…”
Section: ) T −T− Production With T −T− → a H A H Ttmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been a few studies in the literature to discuss how to detect this channel at the LHC [6,21], though more detailed Monte Carlo analysis is needed to confirm how well this channel can be detected. It was also pointed out that it could be very challenging to distinguish this production channel with the top-squark (stop) pair productions predicted by the Minimal Supersymmetric Standard Model (MSSM) with the subsequent decay of stop into top quark and the lightest supersymmetric particle (neutralino) [21].…”
Section: ) T −T− Production With T −T− → a H A H Ttmentioning
confidence: 99%
“…Similarly, the heavy T-odd gauge bosons of the electroweak gauge boson partners are also essential components of the Little Higgs mechanism. Many studies [6,12,17,18,19,20,21,22,23] have been presented in the literature on the detection strategies for T-even and/or T-odd partners of top quark and heavy T-odd gauge bosons at high energy colliders. On the other hand, the T-odd SU(2) partners of SM fermions of the first and second generations received so far little attention with respect to collider phenomenology.…”
Section: Phenomenologymentioning
confidence: 99%
“…Consequently, the same search applies to many different models, but the mass-reach depends on each model's top partner production cross section. Studies of the tt + E miss T signal for new physics have been performed by many groups in various (fully hadronic, single-lepton) channels in recent years [27,29,[31][32][33][34][35][36][37].…”
Section: Jhep07(2012)110mentioning
confidence: 99%
“…This is possible if the partner is also charged under the symmetry that protects the stability of the dark matter particle. Examples are the little Higgs models with T -parity [25][26][27][28], models with the exotic fourth generation and dark matter [29], models with gauged baryon and lepton numbers [30], and so on. Consequently, the same search applies to many different models, but the mass-reach depends on each model's top partner production cross section.…”
Section: Jhep07(2012)110mentioning
confidence: 99%
“…[25,26,31,32]. It was shown that in order to cut off the contributions to the standard model four-fermion interactions from the Goldstone boson loop, there should be a vector-like T-odd doublet partner for every standard model fermionic doublet.…”
Section: Jhep03(2016)098mentioning
confidence: 99%